Perancangan Sistem Informasi Kelengkapan Berkas Klaim BPJS IGD Menggunakan Visual Studio di Rumah Sakit Muhammadiyah Bandung - Erlin Sri Mulyani; Ismi Wanda Agustin; Leni Herfiyanti; Candra Mecca Sufyana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
In the development of sience that is increasingly advance today, checking the completeness of the emergency instalation files at the Muhammadiyah Bandung Hospital is still done manually and reports are still form of manual recording and only using Microsoft Excel. So to create effective and efficient data management and claim processing, an information system for the completeness of the ER file is needed to support BPJS claims using Microsoft Visual Studio and Microsoft Access database. The research method used is qualitative using a descriptive approach using words. Techniques in collecting data are carried out through the interview stage, the observation stage, and the documentation stage in the field of work. Meanwhile, the development method used in this research is the waterfall method through the stages of designing Context Diagrams, Data Flow Diagrams (DFD) Level 0, Entity Relationship Diagrams (ERD), and then implementation. This design is expected to make it easier for officers to display the results of a complete report on whether or not a medical record file, optimal data claims, and improve the quality of medical record services.